Penerapan Websocket pada Sistem Live Chat berbasis Web (Studi Kasus Website Kwikku.com) - Lius Alviando; Adhitya Bhawiyuga; Dany Primanita Kartikasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Live Chat utilizes technology to send messages in real time. As service users increase and the existing system is not yet ready, it can disrupt communication between content creators and community members. The Long Polling method and the Relational Database System that are used use too many resources from the server, it is necessary to update the system using the Websocket protocol. The planning and implementation system created is the design of the system structure and implementation of the Live Chat system development using the Websocket protocol and the programming languages ​​HTML, PHP, CSS and Javascript. The results of testing the system using the load testing method. Based on the results of the analysis that has been carried out with a sample of 100 to 500 users and 3 repetitions, it can be concluded that the Websocket protocol is superior when compared to long polling because it produces smaller delays and has an average efficiency of 52.181%. The Websocket protocol using a non-relational database can be a solution to overcome the problem of high delay on the system